Extensive phospholipid resorption from senescing leaves is not associated with phospholipid substitution in an oligotrophic heath - Grace H. Liang; Orpheus M. Butler; Charles R. Warren (Plant and Soil, 2026)
Background and aims In leaves, ~ 25% of phosphorus (P) is allocated to membrane phospholipids. A significant amount of leaf P is resorbed during leaf senescence to reduce plant P loss upon leaf abscission and fuel the growth of new leaves. High P resorption observed in plants on P depleted soils has been associated with extensive resorption of all P-fractions, including phospholipids, from senescent leaves. This high resorption of phospholipid-P could be associated with the substitution of phospholipids with non-P galactolipids and sulfolipids. Methods We evaluated whether high phospholipid resorption is associated with the substitution of phospholipids with non-P lipids by quantifying the total P, and intact membrane phospholipid, galactolipid and sulfolipid concentrations of mature and senescent leaves of nine co-occurring species (five families) associated with a severely P-poor soil in eastern Australia. Results Phosphorus resorption efficiency, defined as the percentage of P resorbed from senescing leaves per P content in mature leaves, was high across species ( c. 77 – 96%). Total membrane lipid content was substantially lower in senescent leaves than mature leaves across species, although, there was a tendency for resorption efficiency to be greater for non-P lipids ( c. 55 – 95%) than phospholipids ( c. 4 – 87%). Conclusion Exceptionally high rates of total and phospholipid P resorption from senescing leaves is not necessarily associated with the substitution of phospholipids with non-P lipids.

Phosphorus drives adaptive shifts in membrane lipid pools and synthesis between soils - Charles R. Warren; Orpheus M. Butler (Soil Biology and Biochemistry, 2024)

Lipid profiles of plants and soil microbial communities are shaped by soil parent material in Australian sclerophyll forests - Grace H. Liang; Orpheus M. Butler; Charles R. Warren (Plant and Soil, 2024)
Background and aims Plant and soil microbes can reduce their phosphorus (P)-requirements by replacing phospholipids with non-P containing lipids (e.g., galactolipids, sulfolipids, and betaine lipids). There have been few studies of this process in the field (i.e., in natural ecosystems); thus, it is unclear whether a similar replacement of phospholipids with non-P lipids occurs across natural gradients of soil P-availability. Methods We compared the membrane lipid profiles of plant leaves, roots, and soil microbial communities between two adjacent native Australian sclerophyll forest ecosystems—one situated on a severely P-deficient sandstone-derived soil and the other on a comparatively P-rich shale-derived soil. The herbaceous species, Lomandra longifolia, which occurred across both soils was sampled, along with two Myrtaceae tree species associated with each soil type. Results The phospholipid content of plant leaves and soil microbes was two- to three-fold greater in the shale site than the sandstone site, but non-P lipid content did not differ between sites. Conclusion Our results indicate that plants and soil microbes can have a lower investment of P into phospholipids in response to P-deficiency without a concomitant increase in non-P lipid content. Modulations in phospholipid concentration occurred across all plant- and soil microbial-associated phospholipid classes.

Turnover of non-polymeric leaf lipids in a loamy grassland soil - Charles R. Warren; Orpheus M. Butler (Plant and Soil, 2023)
Background Leaves constitute a large input of lipids to soil, yet comparatively little is known about the fate of leaf lipids in soil. Our aim was to explore the initial stages of degradation of leaf lipids, both the loss of intact lipid and subsequent mineralisation. We focussed on intracellular lipids – triacylglycerols implicated in storage, membrane lipids such as phospholipids and galactolipids, and pigments – because they collectively constitute more than 1% of leaf mass. Methods A mixture of U- 13 C lipids was extracted from leaves of wheat grown with 13 CO 2 . The lipid mixture included the range of plant lipids soluble in organic solvent (e.g. free fatty acids, acylglycerols, pigments) but not polymeric lipids such as cutin and suberin. Mineralisation was deduced from 13 CO 2 efflux, while LC–MS examined degradation of intact 13 C lipids. Results There was no delay before lipids were mineralised. Instead, mineralisation was significant within minutes and reached a maximum within three hours. There was rapid loss (i.e. degradation) of a broad range of intact lipids including phospholipids, galactolipids, pigments (chlorophylls), and triacylglycerols. Around two-thirds of added lipid-C was respired over the course of 15 days, with one-third of lipid-C persisting in soil. Conclusions Our study indicates that non-polymeric leaf lipids degrade quickly in soil, yet a fraction of lipid-C likely persisted in degradation products and/or microbial biomass. Persistence of lipid-C probably also reflected the presence of lipids that are more resistant to degradation (e.g. phaeophytins), and a fraction of added lipid being protected (e.g. by interaction with clays). Graphical abstract

The multi-element stoichiometry of wet eucalypt forest is transformed by recent, frequent fire - Orpheus M. Butler; James J. Elser; Tom Lewis; Sarah C. Maunsell; Mehran Rezaei Rashti; Chengrong Chen (Plant and Soil, 2020)

The stoichiometric legacy of fire regime regulates the roles of micro‐organisms and invertebrates in decomposition - Orpheus M. Butler; Tom Lewis; Mehran Rezaei Rashti; Sarah C. Maunsell; James J. Elser; Chengrong Chen (Ecology, 2019)
Decadal‐scale increases in fire frequency have the potential to deplete ecosystems of essential nutrients and consequently impede nutrient‐limited biological processes via stoichiometric imbalance. Decomposition, a fundamental ecosystem function and strong driver of future fire occurrence, is highly sensitive to nutrient availability and is, therefore, particularly important in this context. Here we show that 40 yr of quadrennial (4yB) and biennial (2yB) prescribed burning result in severely P‐ and N‐depleted litter stoichiometry, respectively, relative to fire exclusion. These effects exacerbated the nutrient limitation of microbial activities, constraining litter decomposition by 42.1% (4yB) and 23.6% (2yB) relative to unburned areas. However, invertebrate‐driven decomposition largely compensated for the diminished capacity of micro‐organisms under 4yB, suggesting that invertebrates could have an important stabilizing influence in fire‐affected ecosystems. This effect was strongly positively coupled with the strength of microbial P‐limitation and was not obviously or directly driven by fire regime‐induced changes in invertebrate community assemblage. Together, our results reveal that high‐frequency fire regimes promote nutrient‐poor, carbon‐rich ecosystem stoichiometry and, in doing so, disrupt ecosystem processes and modify the relative functionality of micro‐organisms and invertebrates.

High-frequency fire alters soil and plant chemistry but does not lead to nitrogen-limited growth of Eucalyptus pilularis seedlings - Orpheus M. Butler; Mehran Rezaei Rashti; Tom Lewis; James J. Elser; Chengrong Chen (Plant and Soil, 2018)

The phosphorus‐rich signature of fire in the soil–plant system: a global meta‐analysis - Orpheus M. Butler; James J. Elser; Tom Lewis; Brendan Mackey; Chengrong Chen (Ecology Letters, 2018)
The biogeochemical and stoichiometric signature of vegetation fire may influence post‐fire ecosystem characteristics and the evolution of plant ‘fire traits’. Phosphorus (P), a potentially limiting nutrient in many fire‐prone environments, might be particularly important in this context; however, the effects of fire on P cycling often vary widely. We conducted a global‐scale meta‐analysis using data from 174 soil studies and 39 litter studies, and found that fire led to significantly higher concentrations of soil mineral P as well as significantly lower soil and litter carbon:P and nitrogen:P ratios. These results demonstrate that fire has a P‐rich signature in the soil–plant system that varies with vegetation type. Further, they suggest that burning can ease P limitation and decouple the biogeochemical cycling of P, carbon and nitrogen. These effects resemble a transient reversion to an earlier stage of ecosystem development, and likely underpin at least some of fire's impacts on ecosystems and organisms.

Prescribed fire alters foliar stoichiometry and nutrient resorption in the understorey of a subtropical eucalypt forest - Orpheus M. Butler; Tom Lewis; Chengrong Chen (Plant and Soil, 2017)